Beyond the Chat: An Appsnographic Investigation of UX, BX, and CX in MSME Brands Using ChatGPT - Bioldy, Ersal (Jobmark: Journal of Branding and Marketing Communication, 2026)
The growing integration of artificial intelligence in digital communication has transformed how micro, small, and medium enterprises (MSMEs) develop and experience branding practices. This study proposes an appsnographic approach to investigate the interrelated dimensions of User Experience (UX), Brand Experience (BX), and Consumer Experience (CX) in the context of MSME branding using ChatGPT. Appsnography, as an extension of digital ethnography, enables a multidimensional exploration of technocultural interactions by examining how users engage with applications across techno-physical, sociocultural, communicative, discursive, and mediality dimensions. Adopting a qualitative interpretive approach, this study utilizes appsnographic analysis to capture MSME actors’ lived experiences in interacting with AI-mediated systems for branding purposes. The findings reveal that UX, BX, and CX are not isolated constructs but dynamically interconnected through AI-mediated communication processes. UX reflects usability, accessibility, and cognitive support provided by the system, shaping how MSME actors interact with the technology. BX emerges through the co-creation of brand meaning, in which AI contributes to ideation, storytelling, and the consistency of brand identity. Meanwhile, CX extends beyond end consumers to include MSME actors themselves as “internal consumers,” highlighting how their interactions with ChatGPT as an AI brand influence their perceptions of value creation and customer engagement strategies. The study demonstrates that AI applications function not merely as tools but as active mediators that reshape branding experiences and decision-making processes. The appsnographic lens uncovers the technocultural dynamics underlying these interactions, offering deeper insight into how meaning, experience, and value are constructed in AI-driven environments.